Analisis Dampak Strategi Merger dan Akuisisi terhadap Kinerja dan Keberlangsungan Perusahaan di Indonesia: Studi kasus pada PT GoTo Gojek Tokopedia Tbk - Intan Rani; Anindya Eva Susandari; Rizka Sovyana Devy; Ahmad Nailul Hal Al Karim; Atika Dyah Perwita (Universitas Islam Negeri Mataram, 2026)
This study aims to analyze the impact of merger and acquisition strategies on the financial performance and corporate sustainability of PT GoTo Gojek Tokopedia Tbk. The research employs a quantitative approach with a descriptive-comparative design by comparing financial indicators before and after the merger. Secondary data were obtained from annual and quarterly financial statements for the 2021–2024 period. The results show that post-merger, GoTo experienced consistent net revenue growth from IDR 11.3 trillion in 2022 to IDR 15.89 trillion in 2024. Alongside this growth, the company successfully achieved significant operational efficiency, evidenced by a reduction in operating losses from IDR 36.19 trillion to IDR 10.72 trillion during the same period. Despite a net loss anomaly in 2023 driven by goodwill reversal, the company's capital structure in 2024 indicates a more stable condition with controlled liabilities. The merger strategy has proven to have successfully shifted the company's business orientation from an inefficient hypergrowth phase to a sustainable, structural phase of profitability.